A very rare association of hereditary breast cancer-pregnancy associated, with familial conjoined twin of rarest variety - Biswas, J; Mandal, GK; Mukhopadhyay, AK; Dewan, K; Chakrabarti, S; Dash, S (Nepal Journal of Medical Sciences, 2014)
Pregnancy-associated breast cancer (PABC) is itself a rare entity and even has very rare familial association. Here not only we report a case of PABC in a young lady but another incidental finding of rarest type of conjoined twin classified as dicephalus dibrachius dipus revealed during medical termination of pregnancy. Ultimately at the same time we managed to retrieve a familial association with both neoplastic and non neoplastic conditions from her family pedigree. Nepal Journal of Medical Sciences | Volume 03 | Number 01 | January-June 2014 | Page 68-71 DOI: http://dx.doi.org/10.3126/njms.v3i1.10363